Improving treatment of patients with psychosis in low-and-middle-income countries in Southeast Europe: Results from a hybrid effectiveness-implementation, pragmatic, cluster-randomized clinical trial (IMPULSE) - N. Jovanović; M. Russo; T. Pemovska; J. J. Francis; A. Arenliu; S. Bajraktarov; A. Džubur Kulenović; L. Injac Stevović; A. Novotni; S. Andrić Petrović; T. Radojičić; E. Ribić; et al. (European Psychiatry, 2022)
AbstractBackgroundIn Southeast Europe (SEE) standard treatment of patients with psychosis is largely based on pharmacotherapy with psychosocial interventions rarely available. DIALOG+ is a digital psychosocial intervention designed to make routine care therapeutically effective. This trial simultaneously examined effectiveness of DIALOG+ versus standard care on clinical and social outcomes (Aim 1) and explored intervention fidelity (Aim 2).MethodsA hybrid type II effectiveness–implementation, cluster-randomized trial was conducted in five SEE countries: Bosnia and Herzegovina, Kosovo*, Montenegro, North Macedonia, and Serbia. The intervention was offered to patients six times across 12 months instead of routine care. The outcomes were subjective quality of life (primary), clinical symptoms, satisfaction with services, and economic costs. Intervention fidelity was operationalized as adherence to the protocol in terms of frequency, duration, content, and coverage. Data were analyzed using multilevel regression.ResultsA total of 81 clinicians and 468 patients with psychosis were randomized to DIALOG+ or standard care. The intervention was delivered with high fidelity. The average number of delivered sessions was 5.5 (SD = 2.3) across 12 months. Patients in the intervention arm had better quality of life (MANSA) at 6 months (p = 0.03). No difference was found for other outcomes at 6 months. Due to disruptions caused by the COVID-19 pandemic, 12-month data were not interpretable.ConclusionsDIALOG+ improved subjective quality of life of individuals with psychosis at 6 months (after four sessions), albeit with small effect size. The intervention has the potential to contribute to holistic care of patients with psychosis.